Information Visualization As A Knowledge Integration Tool - Burley, Diana (Journal of Knowledge Management Practice, 2010)
This article advances the argument that information visualization is a valuable tool for knowledge integration activities; including information exploration, integration, and analysis; within complex organizational data environments. In order to effective meet the knowledge integration demands of organizations and their constituents, information visualization tools must be adopted within the context of practical considerations such as the type of data to be examined, the type of visualization desired, the usability of the tool and the capability of the users. Properly considered, information visualization tools will prove to be a valuable knowledge integration tool.